Challenges in the diagnosis of chronic inflammatory demyelinating polyneuropathy. Issue 3 (7th February 2018) - Allen, Jeffrey A.; Gorson, Kenneth C.; Gelinas, Deborah
Abstract: Introduction: We explored adherence to the European Federation of Neurological Societies/Peripheral Nerve Society (EFNS/PNS) guidelines for the diagnosis and treatment of chronic inflammatory demyelinating polyneuropathy (CIDP) by reviewing data from a specialty pharmacy database. Materials and Methods: Clinical and electrophysiologic data were reviewed for 65 consecutive patients treated with intravenous immunoglobulin (IVIG) for CIDP. Three neuromuscular neurologists independently classified cases according to EFNS/PNS criteria as (1) fulfilling CIDP criteria; (2) non‐CIDP (neither clinical nor electrophysiologic criteria met); or (3) unknown (insufficient information). Results: Patients were treated by 31 different community neurologists in 14 states. Only seven patients (11%) met clinical and electrodiagnostic CIDP criteria. The remainder (89%) did not have CIDP (49%) or were unknown (40%). IVIG mean induction dose was 1.25 g/kg, mean maintenance dose 0.79 g/kg, and mean interval between infusions was 23 days. Conclusions: Adherence to EFNS/PNS CIDP diagnostic and treatment guidelines in the general neurologic community was poor. Improved education and awareness of widely available CIDP guidelines are recommended. Abstract : Diagnosing chronic inflammatory demyelinating polyneuropathy (CIDP) can be challenging. We observed that within the general community adherence to European Federation of Neurological Societies/Peripheral Nerve Society (EFNS/PNS) CIDP diagnostic and treatment guidelines was poor. Improved education and awareness of widely available CIDP guidelines are recommended.